Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
at first , you need the sum of both equations . It will be like :
2y= 0 + 2
Y=1
_____
now that you know the value of Y , place it in the one of the equation that you like , forexample i place it in the second equation and find out that the value of x is ( -3/2)
1= 2X+5
-4=2X
X= -2
Hope it helps , good luck ^.^
Y = -2x - 3
Y = -2 + 5
-2x - 3 = 2x + 5
x= -2
y= -2 x (-2) -3
y= 1
( x, y) = (-2, 1)
The answer is (-2, 1)
Y = -2 + 5
-2x - 3 = 2x + 5
x= -2
y= -2 x (-2) -3
y= 1
( x, y) = (-2, 1)
The answer is (-2, 1)
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.